GROWING ORGANIC COTTON WITH BOMS - D.Rakhimova (American Journal Of Agriculture And Horticulture Innovations, 2024)
It is scientifically proven that when Boms organic preparation was applied to the soil at the rate of 300-600 kg/ha before sowing and when cotton was cultivated for without mineral fertilizers, 40.7-41.8 c/ha of cotton can be grown.